2023
DOI: 10.1113/ep090823
|View full text |Cite
|
Sign up to set email alerts
|

Impact of passive heat stress and passive heat acclimation on circulating extracellular vesicles: An exploratory analysis

Abstract: New Findings What is the central question of this study?How does passive heat stress and subsequent heat acclimation affect the circulating concentration of extracellular vesicles? What is the main finding and its importance?Passive heat stress increased the circulating concentration of total and platelet extracellular vesicles. Seven days of hot water immersion did not modify the change in circulating concentrations of extracellular vesicles during passive heat stress. Abstract This retrospective explorator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…In the cerebral venous circulation, we found no change in circulating endothelial microvesicles (either activated or apoptotic) with poikilocapnic hyperthermia. This is in line with all other studies performed in healthy young participants (Coombs et al., 2019; Ravanelli et al., 2023; Wilhelm et al., 2017) where endothelial microvesicles were collected from the peripheral venous circulation. Interestingly, however, Coombs et al.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In the cerebral venous circulation, we found no change in circulating endothelial microvesicles (either activated or apoptotic) with poikilocapnic hyperthermia. This is in line with all other studies performed in healthy young participants (Coombs et al., 2019; Ravanelli et al., 2023; Wilhelm et al., 2017) where endothelial microvesicles were collected from the peripheral venous circulation. Interestingly, however, Coombs et al.…”
Section: Discussionsupporting
confidence: 89%
“…In the cerebral venous circulation, we found no change in circulating endothelial microvesicles (either activated or apoptotic) with poikilocapnic hyperthermia. This is in line with all other studies performed in healthy young participants (Coombs et al, 2019;Ravanelli et al, 2023;Wilhelm et al, 2017) where endothelial microvesicles were collected from the peripheral venous circulation. Interestingly, however, Coombs et al (2019) reported reductions in activated endothelial microvesicles in the venous circulation with passive heating in patients with spinal cord injury, probably attributable to the higher baseline values of venous endothelial microvesicles in this demographic.…”
Section: Microvesicles In Passive Poikilocapnic Hyperthermiasupporting
confidence: 89%
See 3 more Smart Citations